Evolution of Tatarstan’s Local Self-Governments and Challenges They Face - Refly Setiawan (ADALAH, 2019)
Abstract: The laws in the Republic of Tatarstan tend to limit the powers and coverage of local self-government, but Tatarstan’s laws go even further than most in maintaining the “power vertical” which allows state authorities to keep tight control of local self-governments. This control is exercised officially through the laws, and in practice, with financial controls. The local self- governments have difficulty with self financing and are left beholden to state authorities. Because the heads of the 43 administrative districts and 11 large cities in Tartarstan are directly appointed by the president, he exercises rigid control all the way down to the local level. In addition, because these administration heads are allowed to run for parliament, the president has also consolidated considerable power on the level of the republic’s government. In effect, government on the level of the administrative districts and large cities in the republic is completely in the hands of the president and his appointees, who also have financial control over local self- governments.Keywords: Evolution, Tatarstan Local Government, Challenges Faced Abstrak:Undang-undang di Republik Tatarstan cenderung membatasi kekuasaan dan cakupan pemerintahan setempat, tetapi undang-undang Tatarstan bahkan lebih jauh daripada kebanyakan undang-undang lainnya dalam mempertahankan "vertikal kekuasaan" yang memungkinkan otoritas negara untuk menjaga kontrol ketat atas pemerintahan sendiri. Kontrol ini dilakukan secara resmi melalui undang-undang, dan dalam praktiknya, dengan kontrol keuangan. Pemerintah daerah sendiri mengalami kesulitan dengan pembiayaan dan diserahkan kepada otoritas negara. Karena kepala dari 43 distrik administratif dan 11 kota besar di Tartarstan ditunjuk langsung oleh presiden, maka menjalankan kontrol yang kaku sampai ke tingkat lokal. Selain itu, karena para kepala pemerintahan ini diizinkan mencalonkan diri sebagai parlemen, presiden juga telah mengkonsolidasikan kekuasaan yang cukup besar di tingkat pemerintahan republik. Akibatnya, pemerintahan di tingkat distrik administratif dan kota-kota besar di republik sepenuhnya berada di tangan presiden dan orang-orang yang ditunjuknya yang juga memiliki kendali keuangan atas pemerintahan sendiri daerah.Kata Kunci: Evolusi, Pemerintahan Lokal Tatarstan, Tantangan Yang Dihadapi